A boost in the paycheck: Survey evidence on workers' response to the 2011 payroll tax cuts - Grant Graziani; Wilbert van der Klaauw; Basit Zafar (Federal Reserve Bank of New York, 2013)
This paper presents new survey evidence on workers' response to the 2011 payroll tax cuts. While workers intended to spend 10 to 18 percent of their tax-cut income, they reported actually spending 28 to 43 percent of the funds. This is higher than estimates from studies of recent tax cuts, and arguably a consequence of the design of the 2011 tax cuts. The shift to greater consumption than intended is largely unexplained by presentbias or unanticipated shocks, and is likely a consequence of mental accounting. We also use data from a complementary survey to understand the heterogeneous tax-cut response.
Keywords: C83; D91; E21; E62; E65; 330; tax cuts; consumption; liquidity constraints; mental accounts; permanentincome hypothesis; present-bias